Acquire data with LabVIEW To investigate effect of physical parameters on The performance of energy recovery ventilators in buildings - Ngiam, Heng Rui (2016)
The Heating, Ventilation & Air Conditioning (HVAC) system is becoming an essential component in buildings to provide thermal comfort for its occupants. HVAC systems are known to be energy consuming, and one of the method used to mitigate this is to employ an Energy Recovery Ventilator (ERV) to recover energy to offset the load demanded by the HVAC system.